Association between children living with obesity and Mental Health problems: a data analysis of the Welsh Health Survey, UK - Claire Beynon (BMC Public Health, 2023)
Abstract Background Obesity and mental health problems in children are both significant and growing public health issues. There is mixed evidence on the relationship between obesity and mental health in children. This study examines the association between obesity and mental health problems in a nationally representative sample of children using the Welsh Health Survey for Children (n = 11,279 aged 4–15 years). Methods The Chi-square test assessed the difference in the proportion of children reporting abnormal mental health scores (strengths and difficulties score ≥ 20) in children living with obesity (≥ 95 centile for age and sex). Then, a multivarible logistic regression was used to assess any association after accounting for confounding variables. Results There were 1,582 children living with obesity in the study (19.6%). The Chi-square test indicated a significant difference in the proportion of children with abnormal mental health scores in children living with obesity (p = 0.001). This study found a very small but significant positive association between mental health and childhood obesity after accounting for confounding variables, Odds Ratio 1.02 (95%CI: 1.01 to 1.02, p = 0.001). However, socio-economic status was more of a driver. Conclusion The findings of this study show a very small but significant association between childhood obesity and mental health problems. The multivariable logistic regression indicates that the focus must remain on reducing health inequalities as this is a more important driver of child health and well-being. However, as a precautionary measure it may be worth considering if children living with obesity who present for weight-management services may benefit from a review of their mental health status to identify if further support is needed, if capacity allows, and this can be done in a supportive way.